”Så griner vi heldigvis lidt af det”. Ægtepars erfaringer med demens i et hverdagslivs sociologisk perspektiv - Dræbel, Tania; Lund, Kirsten Teglgaard; Liveng, Anne (Nordisk tidsskrift for helseforskning, 2017)
“Fortunately, we laugh a bit about it”. Couples experiences with dementia in an everyday life sociological perspectiveThe article examines changes in the relation between spouses in married couples, where one partner has a dementia diagnosis. Seven qualitative interviews with couples are analyzed with Alfred Schutz sociology of everyday life as a theoretical framework. The analysis asks the question how spouses reinvent routines in an everyday life characterized by a growing unpredictability, and thereby creates new meaningfulness and roles. The analysis illustrates how partners orient themselves in a changed social world, and thereby manage to live an everyday life with dementia. Three modes of relation to each other and to the illness are found, which could partly be understood in connection to the seriousness of the illness: first the couple manage challenges in a marital alliance, later an agreement with new roles and tasks for the partners is established, and towards the final stages of dementia marriage is described as an asymmetrical care relationship.
Keywords: dementia; couples; sociology of everyday life; responsibility; transition; demens; ægtepar; hverdagslivssociologi; ansvar; forandring